La modernidad y el humanismo jesuita del siglo XVIII: la influencia de John Locke en el tratamiento de la justicia de Francisco Javier Alegre - Hugo Rolando Aquino Cruz (Theoría Revista del Colegio de Filosofía, 2016)
The Novohispanic Philosophy is often thought as alien —even opposite— to Modernity. This paper intends to show the clear influence of John Locke in Francisco Javier Alegre’s treatment of justice.